Maximizing the utility of bio-based diisocyanate and chain extenders in crystalline segmented thermoplastic polyester urethanes: effect of polymerization protocol - Li, Shaojun; Jose, Jesmy; Bouzidi, Laziz; Leao, Alcides Lopes [UNESP]; Narine, Suresh S. (Elsevier B.V., 2014)
High molecular weight semi crystalline thermoplastic poly(ester urethanes), TPEUs, were prepared from a vegetable oil-based diisocyanate, aliphatic diol chain extenders and poly(ethylene adipate) macro diol using one-shot, pre-polymer and multi-stage polyaddition methods. The optimized polymerization reaction achieved ultra-high molecular weight TPEUs (>2 million as determined by GPC) in a short time, indicating a very high HPMDI diol reactivity. TPEUs with very well controlled hard segment (HS) and soft segment (SS) blocks were prepared and characterized with DSC, TGA, tensile analysis, and WAXD in order to reveal structure property relationships. A confinement effect that imparts elastomeric properties to otherwise thermoplastic TPEUs was revealed. The confinement extent was found to vary predictably with structure indicating that one can custom engineer tougher polyurethane elastomers by "tuning" soft segment crystallinity with suitable HS block structure. Generally, the HPMDI-based TPEUs exhibited thermal stability and mechanical properties comparable to entirely petroleum-based TPEUs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bio-based diisocyanate; Segmented thermoplastic; Polyester urethane